Do the effects of individual factors on financial risk-taking behavior diversify with financial literacy? - Aydemir, Sibel Dinc; Aren, Selim (EMERALD GROUP PUBLISHING LTD, 2017)
Purpose - This study aims to examine the roles of individual factors on risky investment intention as an indicator of risky financial behavior. Design/methodology/approach - The data were collected from a survey instrument and composed of 496 individuals' responses. The authors exploited structural equation modelling and multigroup structural equation modelling for direct and indirect effects, respectively. Findings - Results indicate that emotional intelligence and locus of control have a positive impact on financial risk-taking, while risk aversion in general has the negative one. Although financial literacy does not have a direct effect on risky financial behavior, it has important role as a moderator variable, interacting with external locus of control. Originality/value - The authors expect this study to contribute into behavioral finance literature in two ways. First, they investigate joint and relative effects of four major factors (i.e. emotional intelligence, locus of control, risk aversion in general and financial literacy) identified in the literature on financial risk-taking of individual investors. Each belongs to a different venue in an individual's psyche and therefore is expected to influence financial risk-taking through different mechanisms. However, the research arguing their roles on the financial risky behavior directly is very limited. Investigating their individual effects is likely to provide unique insights into our understanding of risky financial behavior. Second, the authors also posit and manifest that the effects of the first three of the aforementioned factors on risk-taking intentions are moderated by financial literacy. This finding is likely to provide rather valuable insights pertaining to the emergence of risk-taking behaviors and may shed light on the root reasons behind equivocal findings in previous research regarding the effect of each factor.
Keywords: Emotional intelligence; Financial literacy; Risk aversion; Locus of control; Financial risk taking; BECK DEPRESSION INVENTORY; GENDER-DIFFERENCES; DECISION-MAKING; CONSTRUCT-VALIDITY; EXTERNAL CONTROL; PERCEPTION; LOCUS; ATTITUDE; PERSONALITY; Computer Science